(untitled) (Journal of Information Systems and Technology Management, 2006)
Continuous Auditing, broadly defined as the transformation of internal and external auditing through the application of modern information technology, is being increasingly adopted by firms throughout the world. Organizations ranging from Siemens, HCA, the Royal Canadian Mounted Police, BIPOP Bank and the Internal Revenue Service are developing tools and practices that will bring assurance closer to the transaction and reduce through automation, the cost of auditing. A June 2006 PricewaterhouseCoopers survey finds that 50% of U.S. companies now use continuous auditing techniques and 31% percent of the rest have already made plans to follow suit. In this article we introduce the concepts of CA to a Brazilian audience and discuss its further application there.